Continuous Positive Airway Pressure Treatment in Patients with Alzheimer’s Disease: A Systematic Review. - Pérez-Cabezas, Verónica; Ruiz-Molinero, Carmen; Jiménez-Rejano, José-Jesús; González-Medina, Gloria; Galán Mercant, Alejandro; Martín-Valero, Rocío (MDPI, 2020)
Background: Epidemiological studies have suggested a pathophysiological relationship between obstructive sleep apnea syndrome (OSAS) and Alzheimer’s disease (AD). The aim of this study is to evaluate the treatment of obstructive sleep apnea with continuous positive airway pressure (CPAP) in AD and its relationship with neurocognitive function improvement. Methods: Systematic review conducted following PRISMA’s statements. Relevant studies were searched in MEDLINE, PEDro, SCOPUS, PsycINFO, Web of Science, CINAHL and SportDicus. Original studies in which CPAP treatment was developel in AD patients have been included. Results: 5 studies, 3 RCTs (Randomized controlled trials) and 2 pilot studies. In all RCTs the CPAP intervention was six weeks; 3 weeks of therapeutic CPAP vs. 3 weeks placebo CPAP (pCPAP) followed by 3 weeks tCPAP in patients with AD and OSA. The two pilot studies conducted a follow-up in which the impact on cognitive impairment was measured. Conclusions: CPAP treatment in AD patients decreases excessive daytime sleepiness and improves sleep quality. There are indications that cognitive deterioration function measured with the Mini Mental Scale decreases or evolves to a lesser extent in Alzheimer’s patients treated with CPAP. Caregivers observe stabilization in disease progression with integration of CPAP. More research is needed on the topic presented.
Keywords: Alzheimer, Enfermedad de; Síndrome de apnea del sueño; Alzheimer disease; Continuous positive airway pressure; Neurocognitive function